Second place [large type] - Cusk, Rachel, 1967- (Thorndike press large print basic, 2021)
"A woman invites a famous artist to use her guesthouse in the remote coastal landscape where she lives with her family. Powerfully drawn to his paintings, she believes his vision might penetrate the mystery at the center of her life. But as a long, dry summer sets in, his provocative presence itself becomes an enigma--and disrupts the calm of her secluded household. Second Place, Rachel Cusk's electrifying new novel, is a study of female fate and male privilege, the geometries of human relationships, and the moral questions that animate our lives. It reminds us of art's capacity to uplift--and to destroy"--